Highly sensitive, responsive, and selective iodine gas sensor fabricated using AgI-functionalized graphene - Zhuo Chen; Qiong Lei; Yinchang Ma; Jinrong Wang; Yuan Yan; Jun Yin; Jiaqiang Li; Jie Shen; Guanxing Li; Tingting Pan; Xinglong Dong; Bambar Davaasuren; et al. (Nature Communications)
Abstract Radioactive molecular iodine (I2) is a critical volatile pollutant generated in nuclear energy applications, necessitating sensors that rapidly and selectively detect low concentrations of I2 vapor to protect human health and the environment. In this study, we design and prepare a three-component sensing material comprising reduced graphene oxide (rGO) as the substrate, silver iodide (AgI) particles as active sites, and polystyrene sulfonate as an additive. The AgI particles enable reversible adsorption and conversion of I2 molecules into polyiodides, inducing substantial charge density variation in rGO. This mechanism facilitates exceptional sensitivity and selectivity, ultrafast response and recovery times, and room-temperature operation. A multifunctional sensor prototype fabricated utilizing this material achieves the fastest reported response/recovery times (22/22 seconds in dynamic mode and 4.2/11 seconds in static mode) and a detection limit of 25 ppb, surpassing standards set by the Occupational Safety and Health Administration (OSHA) and the National Institute for Occupational Safety and Health (NIOSH), while outperforming commercial I2 gas sensors. This work provides profound insights into the design of I2 sensing materials and mechanisms for real-world applications.